Engineering Production Control Strategies A Guide to Tailor Strategies that Unite the Merits of Push and Pull - Karrer, Christoph; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Identifying and customizing suitable control strategies is a challenging task, especially when production systems have to cope with variable demands, forecast error, and unstable processes. The focus of this book lies on helping companies with complex and discrete production systems to tailor a production control strategy to their needs. Thereby, the mutual merits of (3z(Bpush(3y (Band (3z(Bpull(3y (Bsystems are taken into account, leading to hybrid strategies. Consequently, the book addresses practitioners who are interested in looking behind the scenes and into the physics of production control. A real-life case study demonstrates the practical applicability of the presented framework.s
Keywords: Economics; Industrial management; Operations research; Economics/Management Science; Management/Business for Professionals; Production/Logistics/Supply Chain Management; Operation Research/Decision Theory